Self-Concept and Achievement in Math Among Australian Primary Students: Gender and Culture Issues - Han, Feifei (Frontiers in Psychology, 2019)
While gender stereotype on math learning and achievement is consistently reported among existing research, these studies predominantly focus on mainstream students with Western cultural backgrounds. There is a dearth of study, which investigates gender effect among Australian Indigenous students. To fill this gap, the present study adopted a multiple-indicator-multiple-indicator-cause approach to structural equation modelling to investigate effects of gender, culture (Indigenous vs. non-Indigenous), and the interaction of the two on students’ self-concept of competence and affect in math, as well as math achievement among Australian primary school students. We found gender stereotype effect not only on students’ self-perceptions of their competence in math but also their actual math performance reflected in their math achievement scores in a standard math test. Boys had higher ratings on math competence and scored more highly on math test than girls. However, the gender stereotype was not found for self-concept of affect. Instead, culture was significantly impacted on self-concept of math affect, indicating that Indigenous students had less enjoyment towards learning math compared with their non-Indigenous peers. Furthermore, significant interaction effects between gender and culture were observed on both self-concept of math competence and math affect. In practice, to enhance Indigenous students’ interest and enjoyment in math learning, educators are suggested to incorporate Indigenous students’ values, beliefs, and traditions when delivering new math knowledge.